PERANCANGAN MEDIA INSTAGRAM SEBAGAI STRATEGI KOMUNIKASI COFFEE SHOP BERGARIS 4 DALAM MENARIK MINAT BELI - Herawati, Eliviana; Purwanti, Angel (LPPM Universitas Putera Batam, 2022)
Coffee Shop Striped 4 is a Coffee Shop located in Batam City that has used social media Instagram as a tool for promotion. Instagram social media can be used as an effective marketing communication strategy if it has the right and clear media design. The aim of the researcher is to analyze the marketing communication strategy through Instagram social media carried out by the 4-line Coffee Shop to attract consumer buying interest. This research method uses a qualitative approach. By interviewing 4 respondents with the purposive sampling method. Interviews were conducted with the owner, administration, IT, and customers of the 4-lined coffee shop in Batam. The analysis in this study uses a data credibility test consisting of a credibility test and a transferability test. The results showed that the Batam City 4 Striped Coffee Shop has 7 design stages on social media: concept, design, content, photos, models, reels, and themes.